Intercropping system of Capsicum annum L. and Tagetes erecta with Mycorrhizal application and cow waste compost - SUSWATI SUSWATI; SERI DEPI; SAISA SAISA; SITI MARDIANA; SAIPUL SIHOTANG (Universitas Syiah Kuala, 2022)
Factors that cause fluctuations in chili production are nutrient content and attack by plant disturbing organisms (PDO). To overcome pest attacks can be done by planting refugia which serves as an alternative that will bring in natural enemies. In addition, the application of cow dung and mycorrhizal compost as biological agents will be able to maintain soil quality and plant growth. This study aims to determine the effect of cow waste compost and arbuscular mycorrhizal fungi (AMF) on the growth and production of red chili plants intercropped with refugia plants. The method was a factorial randomized block design consisting of 2 factors, namely: cow waste compost and AMF. Cow waste compost consists of 5 levels, namely: K0 = without giving cow waste compost, K1 = cow waste compost at a dose of 5 tons/ha-1, K2 = cow waste compost at a dose of 10 tons/ha-1, K3 = cow waste compost at a dose 15 tons/ha-1, K4= cow waste compost dose of 20 tons/ha-1. Meanwhile, arbuscular mycorrhizal fungi consisted of 4 levels, namely: M0= without AMF, M1= AMF 50 kg/ha-1, M2= AMF 100 kg/ha-1, M3= AMF 150 kg/ha-1. The results showed that AMF had a most significant effect on the number of fruits per plant, production per plant, and production per plot, but not significantly different on plant height, some branches, and flowering age of Laris variety red chili. AMF treatment with 150 kg/ha (M3) dose had the highest average value for all observed parameters.